OTTO HASIBUAN’S POLITENESS STRATEGY IN JUDGE SESSION OF MIRNA’S CASE - Pratiwi Tri Utami; Dwi Santoso (Universitas Ahmad Dahlan)
This research explores the forms of politeness strategies in utterances of Otto Hasibuan in Judge Session of Mirna’s case. The research method of this research uses descriptive qualitative method. The subject of the research is Otto Hasibuan’s utterances in Judge Session of Mirna’s case. Furthermore, this research uses the Otto Hasibuan’s utterances containing politeness strategies. In collecting the data, the researcher uses noting and transcribing technique. Then, the data analyzing of this research are categorizing, data classifying, and data analyzing. The researcher watched the Judge Session, wrote down the script, translated the script, identified the Otto’s utterances, classified the script based on the forms of politeness strategies, then analyzed the data. In analyzing the data, it shows that the politeness forms used by Otto Hasibuan have ten typical speech acts: warning, asking (for permission), questioning, requesting, suggesting, agreeing, informing, criticizing, respecting, and thanking, which are categorized into five maxims: tact maxim, agreement maxims, opinion-reticence maxim, approbation maxim, and obligation maxim.